The Economic Viability of Associated Gas Investment in Iraq During the period (2012-2021) - Abbas Mohsen *, Maysam; Mohammed Rasheed, Thaer (Journal of Economics and Administrative Sciences, 2024)
Purpose: Examine the feasibility of investing in and processing associated gas and the impact of increased investment in flaring associated gas on the Iraqi economy, in addition to knowing the quantities of gas produced, invested and burned in Iraq Also calculating the costs that Iraq loses due to gas flaring During the research period (2012-2021).Theoretical framework: The research addresses the feasibility of investing in associated gas from oil and its impact on the Iraqi economy, given its abundant availability. The research problem revolves around whether Iraq can achieve self-sufficiency in gas production and whether it can reach the status of a natural gas exporting country in the coming years, as the Iraqi government aspires to achieve as soon as possible.Design/methodology/approach: The available data on associated gas in Iraq during the period (2012-2021) were used to determine the volume of gas production, the amount burned, the volume of investment, and the material losses resulting from its burning.Findings: The results show the importance of investing in gas in Iraq, as it represents an important resource that can be used to achieve self-sufficiency in energy, as gas represents a raw material for many industries such as petrochemicals, fertilizers, and others...Research, Practical & Social implications: Iraq primarily relies on two main sources for its energy useو oil and natural gas, due to their abundant availability. Through these sources, electrical energy is generated, which is the main driver for all vital installations in Iraq.Originality/value: We propose a future research agenda and highlight investment in associated gas and its impact on the Iraqi economy, in addition to providing realistic recommendations aimed at investing in associated gas, achieving economic goals, and reaching the appropriate global position considering the availability of this important resource.